INTERLEUKIN-2 – AND INTERFERON-ALPHA- INDUCED CHANGES OF PERIPHERAL BLOOD LYMPHOCYTE SUBPOPULATIONS IN CHILDREN WITH ADVANCED MALIGNANCIES, TREATED WITH CHEMOTHERAPY AND WHOLE BODY HYPERTHERMIA - R. S. Ismail-zade; M. V. Belevtsev; M. P. Potapnev; V. P. Savitskiy; E. A. Zhavrid; S. E. Buglova (Медицинская иммунология, 2014)
Abstract. The effect of cytokine preparations (Interleukin-2/IL-2/Proleukin and interferon-alpha/IFN-α 2b/ Intron A) on immune cell subpopulations has been studied in the children suffering with advanced malignancies during intensive chemotherapy cycles combined with whole body hyperthermia (thermochemotherapy). It was shown that IFN-α 2b promotes recovery of peripheral lymphocyte counts in the patients. However, no sufficient changes were observed for the lymphocyte subpopulations. Furthermore, more profound lymphopenia along with increased contents of activated (CD25+, HLA-DR+) T cells occurs in a group of children treated with IL-2, as compared to the patients who received IFN-α 2b. Besides that, some differential effects upon the CD4+/CD8+ T-cell ratios were observed in the patients treated with Proleukin or Intron A, with a tendency to increase in CD4+ T-cells for the patients treated with IL-2. It was concluded that differential immunomodulatory mechanisms mediate the effects of IL-2 and IFN-α 2b in the patients with malignancies undergoing combined chemobiotherapy with whole-body hyperthermia.